Diversification des élites et repositionnement organisationnel - Annabelle Allouch; Hélène Buisson-Fenet (Les éditions de la Maison des sciences de l'Homme, 2008)
Whereas American implementations of affirmative action focus attention on the process of democratization in Higher Education, some European educational systems and the model of social opening policies seem up to now neglected by analysts. If France and Britain share a common statement on elitism - although they define it according to very different principles (meritocracy through academic performances versus hereditary transmission of an ethos), a synthetic comparison of « positive discrimination » and outreach allows us to define the political conditions (and debates) of these policies implementations, now targeting « individuals in context » rather than the usual macrosocial or territorial categories. Regulation patterns reveal to some extent -and although still unstable- a general willingness for "potential and ability assessment", which would make both Higher education recruitment systems less socially exclusive.